The association between self-efficacy and sick-leave among men and women: a cross-sectional study of the general working population in Sweden (Epidemiology, Biostatistics, and Public Health, 2022)
Background: The aim of this study was to investigate if low self-efficacy was associated with increased risk for sickness absence, in a general population of employed women and men. The aim was also to analyse differences in self-efficacy concerning age, education, income, and socio-economic position.Methods: This cross-sectional study was based on data collected in western Sweden, 2008. The study population consisted of 2,900 employed sick-listed individuals (E-SL) and 2,649 random working population individuals (R-WP). Both mailed questionnaire, including the General Self-Efficacy Scale (GSE) and register data on age, education, income and socio-economic position were used. A continuous mean score of the total GSE was calculated for each individual. A low GSE-score indicated low general self-efficacy.Results: Lower general self-efficacy had an increased odds ratio (OR) of belonging to a sick-listed general working population among both men (OR=1.60; 95% CI 1.32–1.94) and women (OR=1.26; 95% CI 1.08–1.47). The OR remained significant after adjustments for socio-demographic variables. Yet, men in the R-WP and women in both the R-WP and E-SL with lower education, income or socio-economic position had lower general self-efficacy compared with those in each cohort with higher education, income or socio-economic position.Conclusions: Low self-efficacy was associated with increased probability to belong to a sick-listed general working population. Although more research is needed, it seems highly relevant to take both self-efficacy and socio-economic factors into account, in preventive and rehabilitation work targeting persons on sickness absence.